Reduplication cyst of appendix with mucinous carcinoma and Müllerian metaplasia: a case report. Issue 7 (1st July 2002) - Sington, J D; Warren, B F; Manek, S
Abstract : This report describes a case of mucinous carcinoma and Müllerian metaplasia arising within an appendiceal duplication cyst found incidentally during an emergency Caesarian section. Intestinal duplication cysts are rare and although there are occasional reports of malignant transformation, this is the first case where Müllerian metaplasia was found concurrently with a malignancy. There was no previous history of endometriosis and no other abnormalities were found at surgery. Treatment included surgical excision. The patient is alive and well two years after removal of the cyst.